Digital Literacy and Islamic Sharia Values as A New Perspective of Preventing OGBV - Fitri, Ainal; Triantoro, Dony Arung; Nurrahmi, Febri; Haekal, Muhammad (Program Studi Ilmu Komunikasi, 2024)
This research aims to explore the digital literacy position of students using social media in Aceh and see its relation to the issue of OGBV as victims and bystanders. This research also investigates the relationship between digital literacy, OGBV, and the role of Sharia Law in Aceh, which may provide a new perspective for preventing OGBV in Indonesia, considering the paucity of previous studies correlating those three aspects. This research utilized the concept of Digital Literacy created by Paul Gilster and used the Four-Component Digital Literacy Model developed by Alexander V. Sharikov. This research was conducted using a qualitative approach. Researchers conducted in-depth interviews with nine students and analyzed them using Thematic Analysis. The results revealed that most participants do not have a knowledge base about OGBV, which has implications for their digital literacy capital, especially in identifying various OGBV variants and how to protect personal data on social media. In addition, Islamic law influences participants' digital literacy in dealing with OGBV. However, participants' knowledge of Sharia law values regarding safe and responsible digital interaction patterns has yet to develop comprehensively.